2022
DOI: 10.21037/qims-22-156
|View full text |Cite
|
Sign up to set email alerts
|

MR neurography of lumbosacral nerve roots for differentiating chronic inflammatory demyelinating polyneuropathy from acquired axonal polyneuropathies: a cross-sectional study

Abstract: Background: Magnetic resonance (MR) neurography is an imaging technique focused on the peripheral nerves. Its role in the diagnosis and differential diagnosis of chronic inflammatory demyelinating polyneuropathy (CIDP) has yet to be investigated. This study explored the value of MR neurography in identifying CIDP and differentiating it from acquired axonal polyneuropathies. Methods:In this study, 20 patients with CIDP, 10 patients with acquired axonal polyneuropathies, and 20 healthy controls were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, there are no other reports on DTI findings from the brain in patients with CIDP. On the other hand, there are several studies on the application of DTI in the assessment of peripheral nerves in conditions of entrapment neuropathy, tumors, and traumatic injury ( 57 ) and in the assessment of the rate of damage in CIDP and axonal polyneuropathies ( 58 , 59 ). DTI and DTT of the peripheral nerves have the potential to introduce novel functional information beyond conventional, qualitative MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are no other reports on DTI findings from the brain in patients with CIDP. On the other hand, there are several studies on the application of DTI in the assessment of peripheral nerves in conditions of entrapment neuropathy, tumors, and traumatic injury ( 57 ) and in the assessment of the rate of damage in CIDP and axonal polyneuropathies ( 58 , 59 ). DTI and DTT of the peripheral nerves have the potential to introduce novel functional information beyond conventional, qualitative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…DTI and DTT of the peripheral nerves have the potential to introduce novel functional information beyond conventional, qualitative MRI. DTI of proximal nerve segments may be useful for estimating the proximal axonal degeneration burden in patients with peripheral neuropathies ( 57 59 ). Wu et al concluded that the cross-sectional area (CSA) and apparent diffusion coefficient (ADC) values of the lumbosacral nerve roots could help identify patients with CIDP and further distinguish them from patients with axonal polyneuropathies ( 59 ).…”
Section: Discussionmentioning
confidence: 99%